Leadership issues in West Indies cricket : a theoretical analysis of leadership styles of a purposive group of captains - Corbin, Eddie (2005)
Provides a theoretical analysis of the leadership styles and associated behaviours of a purposive group of West Indies cricket captains who excelled during their tenure with the West Indies cricket team.